2006
DOI: 10.1002/kin.20150
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the kinetics of imidazolium fluorochromate oxidation of some meta‐ and para‐substituted anilines in nonaqueous media

Abstract: The imidazolium fluorochromate (IFC) oxidation of meta-and para-substituted anilines, in seven organic solvents, in the presence of p-toluenesulfonic acid (TsOH) is first order in IFC and TsOH and is zero order with respect to substrate. The IFC oxidation of 15 meta-and para-substituted anilines at 299-322 K complies with the isokinetic relationship but not to any of the linear free energy relationships; the isokinetic temperature lies within the experimental range. The specific rate of oxidizing species-anili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
4
16
0
Order By: Relevance
“…The values of the reaction constant, ρ, were found to be negative, which confirms the formation of a positively charged transition state. The reaction constants obtained in the present study are comparable to those of previously reported oxidation of anilines by various oxidants (percarbonate, ρ = −2.7 [28]; perborate, ρ = −3.0 [29]; pyridinium chlorochromate, [30], and imidazolium fluorochromate, ρ = −2.22 [31]). …”
Section: Structure-reactivity Correlationsupporting
confidence: 90%
“…The values of the reaction constant, ρ, were found to be negative, which confirms the formation of a positively charged transition state. The reaction constants obtained in the present study are comparable to those of previously reported oxidation of anilines by various oxidants (percarbonate, ρ = −2.7 [28]; perborate, ρ = −3.0 [29]; pyridinium chlorochromate, [30], and imidazolium fluorochromate, ρ = −2.22 [31]). …”
Section: Structure-reactivity Correlationsupporting
confidence: 90%
“…This was in agreement with the literature value 19 . The melting point of the product obtained is 68 o C which is in agreement with literature value 16, 20 .…”
Section: Methodssupporting
confidence: 91%
“…Catalysis by p-toluenesulfonic acid suggested protonation of IFC species rather than the benzylamine molecule, which would have resulted in rate retardation. Parallel observations were made in the oxidation of substituted anilines by the same oxidant [4]. The participation of protonated chromium species in Cr(VI) oxidations is well known [15].…”
Section: Product Analysismentioning
confidence: 87%
“…The negative sign of the coefficients of the α term suggests that the specific interaction between the reactants and the solvent (through the HBD property) is relatively more than that between the transition state and the solvent. Since 2-methylpropan-2-ol is a typical HBD solvent, it forms a sheath of solvent shell around the lone pair of electrons residing on N-atom (as shown below) through H-bond donation or, in other words, acts as a very mild form of a blocking reagent [4,7]. Thus restricting the approach of the oxidant molecule to form the transition state and consequently retarded the rate of the oxidation.…”
Section: Solvent-reactivity Correlationmentioning
confidence: 97%